Examining of triboelectric phenomena on wear properties of metal-polymeric frictional couples - Kryshtopa, S.; Kryshtopa, L.; Kozak, F.; Maslennikov, M. (Problems of Tribology, 2019)
The influence of triboelectric phenomena on the wear-friction properties of microasperities contacts of friction couples of drum – shoe brakes was explored. As a result of the conducted research into the wear-friction properties of metal-polymeric frictional couples of braking devices under laboratory and operational conditions at the nano-, micro- and millilevel during triboelectric interaction, the regularities of changes were established: - of magnitudes of the contact difference of potentials of frictional couples "grey cast iron – polymers" of the drum-shoe brake on the surface temperature of linings and specific loads; -of circulating thermal and tribocurrents on the time of friction interaction of frictional couples "cast iron – polymers" and "steel – polymers" at different sliding velocities; - of generated tribocurrents in the contact of two-layered structures "steel – polymer" and circulating tribocurrents through the three-layered structure "steel – polymer – steel" on the surface temperatures